Hydrothermal deconstruction of single-use personal protective equipment during the COVID-19 pandemic. (November 2022) - Javid, Faisal; Xin, Xing; Derraik, José G.B.; Anderson, William A.; Anderson, Yvonne; Baroutian, Saeid
Graphical abstract: Highlights: Up to 98% of single-use PPE items was deconstructed. Up to 547 mg/L ammonia was detected in the resulting reaction mixture. Volatile fatty acids, primarily acetic acid up to 8974 mg/L was produced. Carbon dioxide and oxygen were the main gaseous products in the off-gas stream. Abstract: To minimise the transmission of the SARS-CoV-2 virus, there has been a substantial increase in the production and usage of synthetic personal protective equipment (PPE) globally. Consequently, single-use PPE have been widely adopted without appropriate regulations for their disposal, leading to extensive environmental contamination worldwide. This study investigates the non-catalytic hydrothermal deconstruction of different PPE items, including isolation gowns, gloves, goggles, face shields, surgical masks, and filtering-facepiece respirators. The selected PPE items were subjected to hydrothermal deconstruction for 90 min in the presence of 30-bar initial oxygen pressure, at temperatures ranging between 250 °C and 350 °C. The solid content in form of total suspended solids (TSS) was reduced up to 97.6%. The total chemical oxygen demand (tCOD) and soluble chemical oxygen demand (sCOD) decreased with increasing deconstruction temperature, and at 350 °C the lowest tCOD and sCOD content of 546.6 mg/L and 470 mg/L, respectively, was achieved. Short-chained volatile fatty acids were produced after 90 min of deconstruction, predominantly acetic acid at concentrations up to 8974 mg/L. Ammonia nitrogen content ( NH3 –N ) of up to 542.6 mg/L was also detected. Carbon dioxide (CO2 ) and unreacted oxygen (O2 ) were the main gaseous by-products at up to 15.6% (w/w) and 88.7% (w/w), respectively. The findings suggest that non-catalytic hydrothermal deconstruction is a viable option to process and manage PPE waste.